Consociational Democracy and Its Impact on Political Stability in Iraq (An Analytical Study) - Hussein, Asst.L. qanie Yassin Hussein; حمەرشید, م.م. کاظم روستم حمەرشید (Sulaimani Journal for Humanities, 2025)
In general, consociational democracy can have a positive impact on political stability by promoting cooperation and compromise among different groups. It can help reduce polarization, build trust, and create a more cohesive and stable society. However, implementing consociational democracy can pose a challenge to the political process in the country, as it requires a high degree of political will and commitment from all parties involved.Consociational democracy in Iraq is considered a model of significant political transformation, aiming to achieve balance and understanding among various groups and parties. This approach focuses on the necessity of building communication bridges and ensuring the participation of all parties in decision-making. Despite the challenges that may arise in applying this model, its impact is evident in achieving political stability by providing opportunities for inclusive representation and promoting understanding among the components of Iraqi society.Iraq is among the countries that have witnessed significant political transformations, and achieving political stability there has become a subject of debate. This research focuses on studying the impact of consociational democracy on political stability in Iraq, with an emphasis on how to achieve balance among different groups and parties. Through this study, we attempt to determine the extent of consociational democracy's impact on political stability in Iraq, particularly in the participation of various groups in the political balancing process. Consociationalism emphasizes the sharing of power among different groups within the government, allowing them to have a say in decision-making. This approach aims to prevent the dominance of one group over others and to create a stable political environment.